Students’ Perception of the Use Contextual Teaching and Learning to Improve Speaking Skill - Wahyu Trimastuti; Santy Christinawati (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2021)
The main objective of the research is to find out whether contextual teaching and learning can improve speaking skill or not. The descriptive quantitative method was employed in this research. The population of the research was the students of accounting computerized of Piksi Ganesha Polytechnic. The samples of the research were accounting computerized of AKE-K31/16 which consists of twenty four students. To collect the data, the writer used questionnaire to find out the students’ perception toward the use of contextual teaching and learning and speaking test to know whether the final test score of the students have a significant progress or not. Contextual teaching and learning offers a highly natural and powerful means to convey, learn, and retain information. It can be seen that students were encouraged to be actively and motivately in every activity. Based on the reserach finding, it can be conclude that contextual teaching and learning can improve speaking skill and give good atmosphere in teaching learning process. Therefore, it is suggested that: (1) it is better to apply contextual teaching and learning to improve speaking skill; (2) the students are expected to be more active in the teaching and learning process in order to improve their speaking skill; (3) this result of the study can be used as a beginning step to conduct a further research.